Catatonia: A Common Cause of Late Regression in Autism - Ghaziuddin, Mohammad (Frontiers in Psychiatry, 2021)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by social communication deficits and restricted interests and behaviors which begin very early in life. In about a quarter of cases, the symptoms emerge about 18-24 months after a period of normal development, a phenomenon commonly described as early regression. However, marked functional decline can also occur in persons with autism after a relatively stable childhood. As opposed to early regression, which occurs in normally developing children, late regression occurs in adolescents with an established diagnosis of autism. Apart from their occasional mention in the literature, these individuals have not been examined systematically. This Brief Report describes the presentation, comorbidity and short-term outcome of 20 persons with ASD who developed late regression. The mean age of onset of regression was 13 years. One of the earliest symptoms was an increase in obsessive slowing and compulsive rituals. Other symptoms included motor abnormalities, aggression and mood disturbance. The most common comorbid disorder was catatonia occurring in 17 patients. Despite treatment with several modalities, the outcome was often suboptimal. These findings suggest that catatonia is a common cause of late regression in persons with autism. Clinical and research implications are discussed.